Humanising leadership: transforming the education landscape - Azman, Amelia Wong; Abdul Ghani, Zurina; Musa, Muhammad Adli; Wan Zulkifle, Wan Zahidah; Mohd Mustafah, Yasir (Office of Knowledge for Change and Advancement (KCA), 2023)
This book argues that humanising leadership is pertinent to nurture leaders who would become enablers to the strategic implementation and fair distribution of resources that would put an end to suppression, oppression and discrimination. Acknowledging that there are various ‘styles’ of leadership, the ultimate purpose is to provide solutions for the predicaments that humanity face which require addressing issues related to the five Ps of the sustainable development goals – people, prosperity, planet, partnership and peace. Maqāṣid al-Sharīʿah can potentially provide a framework to achieve this aim. Spirituality can play an important role as God-consciousness will ensure that leaders recognise that they are responsible and accountable for their actions as authority is not a privilege but a ‘burden’. In relation the education landscape, humanisation requires going back to the very fundamental question of what the purpose of education is - 'transforming oneself and society to be better’. A model for humanising leadership can be developed from Prophetic guidance as Muhammad ﷺ himself was a leader in various capacities.